Exploring an online metacognitive intervention on young and mature employees: A preliminary study (Journal of Applied Learning and Teaching, 2024)
With sufficient metacognitive knowledge and action, employees are better equipped in their time and work management, avoiding any unproductive behaviour. Metacognitive strategies thus equip them with the need to learn and develop their career resilience, especially the young and mature working adults. As there are limited intervention studies exploring the metacognition of both young and mature employees, the present study investigated a metacognitive intervention to promote adaptability and career resilience. It explored the metacognitive strategies that include planning, monitoring and evaluating and examined the differences of various outcome variables (e.g., adaptability, critical thinking and career resilience). A total of 71 participants were recruited, and they underwent an eight-week metacognitive intervention. Pre- and post-questionnaires were administered before and after the intervention. Key findings indicated that the group difference was insignificant, suggesting the importance of metacognitive strategies in supporting adaptability and career resilience for young and mature employees. Finally, limitations to the study were presented, and recommendations were made for future workplace research and practice.